Level 1 of Entrustable Professional Activities in adult echocardiography: a position statement from the EACVI regarding the training and competence requirements for selecting and interpreting echocardiographic examinations. (12th August 2021) - Stankovic, Ivan; Muraru, Denisa; Fox, Kevin; Di Salvo, Giovanni; Hasselberg, Nina E; Breithardt, Ole-A; Hansen, Tina B; Neskovic, Aleksandar N; Gargani, Luna; Cosyns, Bernard; Edvardsen, Thor
Abstract: The goal of Level 1 training in echocardiography is to enable the trainee to select echocardiography appropriately for the evaluation of a specific clinical question, and then to interpret the report. It is not the goal of Level 1 training to teach how to perform the examination itself—that is the goal of higher levels of training. However, understanding the principles, indications, and findings of this crucial technique is valuable to many medical professionals including outside cardiology. This should be seen as part of a general understanding of cardiac imaging modalities. The purpose of this position statement is to define the scope and outline the general requirements for Level 1 training and competence in echocardiography. Moreover, the document aims to make a clear distinction between Level 1 competence in echocardiography and focus cardiac ultrasound (FoCUS). Graphical Abstract: